Life spanning murine gene expression profiles in relation to chronological and pathological aging in multiple organs. Issue 5 (14th July 2013) - Jonker, Martijs J.; Melis, Joost P. M.; Kuiper, Raoul V.; van der Hoeven, Tessa V.; Wackers, Paul F. K.; Robinson, Joke; van der Horst, Gijsbertus T. J.; Dollé, Martijn E. T.; Vijg, Jan; Breit, Timo M.; Hoeijmakers, Jan H. J.; van Steeg, Harry
Summary: Aging and age‐related pathology is a result of a still incompletely understood intricate web of molecular and cellular processes. We present a C57BL/6J female mice in vivo aging study of five organs (liver, kidney, spleen, lung, and brain), in which we compare genome‐wide gene expression profiles during chronological aging with pathological changes throughout the entire murine life span (13, 26, 52, 78, 104, and 130 weeks). Relating gene expression changes to chronological aging revealed many differentially expressed genes (DEGs), and altered gene sets (AGSs) were found in most organs, indicative of intraorgan generic aging processes. However, only ≤ 1% of these DEGs are found in all organs. For each organ, at least one of 18 tested pathological parameters showed a good age‐predictive value, albeit with much inter‐ and intraindividual (organ) variation. Relating gene expression changes to pathology‐related aging revealed correlated genes and gene sets, which made it possible to characterize the difference between biological and chronological aging. In liver, kidney, and brain, a limited number of overlapping pathology‐related AGSs were found. Immune responses appeared to be common, yet the changes were specific in most organs. Furthermore, changes were observed in energy homeostasis, reactive oxygen species, cell cycle, cell motility, and DNA damage. Comparison of chronological and pathology‐related AGSs revealed substantial overlap and interesting differences. For example, the presence of immune processes in liver pathology‐related AGSs that were not detected in chronological aging. The many cellular processes that are only found employing aging‐related pathology could provide important new insights into the progress of aging.